Outcomes reported on the management of COPD exacerbations: a systematic survey of randomised controlled trials - Mathioudakis, Alexander G. (ERJ Open Res, 2019)
Randomised controlled trials (RCTs) evaluating the management of acute exacerbations of chronic obstructive pulmonary disease (COPD) report heterogeneous outcome measures, thus rendering their results incomparable, complicating their translation into clinical practice. As a first step in the development of a core outcome set that will aim to homogenise outcome measures in future RCTs, we assessed the outcomes reported in recent relevant RCTs and systematic reviews. We conducted a methodological systematic review (https://www.crd.york.ac.uk/prospero/ registration number CRD42016052437) of RCTs and systematic reviews on COPD exacerbation management indexed on Medline and PubMed during the last decade. We evaluated their methodology, specifically focusing on the reported outcome measures. Based on 123 RCTs and 38 systematic reviews, we found significant variability in the outcomes reported and in their definition. Mortality, which was assessed in 82% of the included trials, was the most frequently assessed outcome, followed by the rate of treatment success or failure (63%), adverse events (59%), health status, symptoms and quality of life (59%), lung function (47%), and duration of exacerbations (42%). The significant heterogeneity in the selection and definition of outcome measures in RCTs and systematic reviews limits the interpretability and comparability of their results, and warrants the development of a core outcome set for COPD exacerbations management.